2020
DOI: 10.18016/ksutarimdoga.vi.593757
|View full text |Cite
|
Sign up to set email alerts
|

Bitlis İli Anadolu Mandası Yetiştiricilerinin Manda Besleme ve Ürünlerinden Faydalanma ve Pazarlama Olanaklarına Yönelik Görüşleri

Abstract: This study was performed to determine the production practices and the general structural characteristics of Anatolian buffalo farmers in Güroymak and Mutki regions of Bitlis province. The research group of this study consisted of 136 of breeders reared Anatolian buffalo in these regions and was questioned from 85 item of question at total. Obtained data were analyzed in Statistical Analyzes System (SAS). In the research, it was detected that buffalo breeding in Bitlis city was mainly conducted by middle age (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Kahramanmaraş ili topraklarında yapılan diğer toprak analizlerinde ise, toprakların genellikle nötr ve hafif alkalin reaksiyonda, hafif tuzlu, kireç içeriğinin yüksek, organik madde içeriğinin düşük, bitkiye yarayışlı potasyumun yeterli, fosforun ise analizlerin yarısına yakınında yeterli çıktığı bildirilmiştir (Yılmaz 2020). Karagöktaş'ın (2012) Kahramanmaraş, Afşin-Elbistan tarım arazilerinde yaptığı analizlerde, toprakların saturasyonlarının % 52-74 arasında, toplam tuz miktarının % 0.07-0.25 arasında, bitkiye yarayışlı fosforun 8.9-116.5 mg/kg arasında, bitkiye yarayışlı potasyumun 119-1256 mg/kg arasında olduğu belirtilmiştir.…”
Section: Bulgular Ve Tartişmaunclassified
“…Kahramanmaraş ili topraklarında yapılan diğer toprak analizlerinde ise, toprakların genellikle nötr ve hafif alkalin reaksiyonda, hafif tuzlu, kireç içeriğinin yüksek, organik madde içeriğinin düşük, bitkiye yarayışlı potasyumun yeterli, fosforun ise analizlerin yarısına yakınında yeterli çıktığı bildirilmiştir (Yılmaz 2020). Karagöktaş'ın (2012) Kahramanmaraş, Afşin-Elbistan tarım arazilerinde yaptığı analizlerde, toprakların saturasyonlarının % 52-74 arasında, toplam tuz miktarının % 0.07-0.25 arasında, bitkiye yarayışlı fosforun 8.9-116.5 mg/kg arasında, bitkiye yarayışlı potasyumun 119-1256 mg/kg arasında olduğu belirtilmiştir.…”
Section: Bulgular Ve Tartişmaunclassified
“…Altınbaş (2003), in the study conducted in the province of Bartın, determined that the water buffaloes in the region benefited from the pastures for 6.6 months. In their study, Çiftçi and Yılmaz (2020) determined the annual average duration for the breeders for rangeland utilization as 1-2 months, 3-6 months, and 7-8 months, and determined the utilization rates from the pasture as 0.00%, 66.91%, and 33.09%, respectively. Kaptan (2019) has reported that 42% of the breeders benefited from the pasture for 7-8 68% 32% With Other Species Only Water Buffaloes months, and 55% for 9 months or more.…”
Section: Information On Utilization Of Pasture and Shepherd Usementioning
confidence: 99%
“…It was determined that foot and mouth disease (98.6%) and lice (17.7%) are the most common diseases seen in farms. Çiftçi and Yılmaz (2020) have stated that 77.21% of the businesses encountered parasites and foot and mouth disease, 8.82% encountered parasitic diseases, brucella, and foot and mouth disease, and 13.97% encountered digestive system problems, parasites, foot, and mouth disease and strokes. Özger (2018) have reported that, in Iğdır, the most common diseases in businesses were 65% foot and mouth disease, 17.5% foot and mouth disease and smallpox, and 10% foot and mouth disease and jaundice.…”
Section: Care and Health Applicationsmentioning
confidence: 99%
See 1 more Smart Citation